Penguatan Wakaf Produktif Berbasis Hutan Wakaf Melalui Program Konservasi dan Reboisasi untuk Mendukung SDGs - Fajar Rachmad Dwi Miarsa; Ahmad Heru Romadhon; Muhammad Alief Nur; Moch. Gufron Fajar Rezki; Nonaqu Beautyla Putri Dharmawan (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The environmental crisis marked by land degradation and declining ecosystem quality demands an alternative approach that is sustainable and based on community participation. One of the instruments that has great potential but has not been optimally utilized is waqf, especially environment-based productive waqf. This community service activity aims to strengthen the role of waqf forests as a sustainable productive waqf instrument through conservation and reforestation programs in the Waqf Forest of the Ma'arif Education and Social Foundation (YPM) Ngembat Village, Gondang District, Mojokerto Regency. The method of implementing activities uses a participatory approach by involving waqf managers and local communities in conservation actions in the form of planting tree seedlings in waqf forest areas. Activity data was obtained through field observation and documentation, then analyzed in a qualitative descriptive manner. The results of the activity show that waqf forests are able to function as a means of environmental conservation as well as a medium for community empowerment based on religious values. Community participation has increased and waqf forests contribute to efforts to protect terrestrial ecosystems and achieve the Sustainable Development Goals (SDGs). This activity emphasizes that waqf can be developed as a strategic instrument in environmental conservation and sustainable development.